Planejamento da participação política como parte integrante do planejamento pessoal - Verardi, Mariane (2009)
This paper aims to develop a Model of Planning of Political Participation with an emphasis on political represent that optimizes the Personal Planning. To do so, it uses the approach of a qualitative research, by means of a technique of bibliographical research. So that it can reach its goals, this study analyzes and describes the main models of Planning of Political Participation existing in the literature. The proposed model is formed by 9 (nine) fields: Research, Position, Politics, Organization, Finances, Administration, Propaganda, Mobilization and Evaluation. To make it valid, five professionals (a researcher, three coordinators of election polls and a political campaign coordinator who is also a researcher) were interviewed. After the interviews, the collected data from the secondary sources were analyzed and interpreted. Finally, the necessary changes were made in the initially developed model.